PERLINDUNGAN HUKUM TERHADAP PRIVACY DARI SPAMMING BERDASARKAN UNDANG-UNDANG NO. 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Tansah Rahmatullah (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2015)
Spamming, as an act of dissemination of unsolicited electronic message, has now become a real phenomenon asthe result of the development in information and communication technology and caused a new legal issues. Therefore, this research was intended to find out how spamming can be categorized into a breach over privacy, and how legal protection fromspamming can be implemented according to the Law Number 11 year 2008 about Information and Electronic Transaction. Based on the results of this research byusing normative juridical approach and comparative juridical approach can be seen that The Law of Number11 of 2008 on Electronic Information And Transactions(ITE) has no determined regulation that especially regulates spamming cases. In Article 26, Article 28 and 33 which is the subject of the study of principal problem studied have obscurity rules. Therefore, Government needs to formulize a legal system specifically intended to regulate spam cases and the act of spammingdue to many people have become the victims of it and resulted in huge loss. In addition of policy and regulation, there is user education factor becomes and important aspect in order to avoid the risk ofmisuse of personal data.